Encouraging Women Entrepreneurship to Join the Global Market (Case study on Fashion Industry in West Java) - Mashithoh, Heriyanni; Ginting, Ginta (APMBA (Asia Pacific Management and Business Application), 2016)
The integration of global market has opened today for the foreign products to entry any countries and has threatened the future of women entrepreneurs. Women entrepreneurs have to compete with foreign businessmen who have superiority in terms of funds, technology, infrastructure, market information and government support. Indonesia is one of developing country who encourages the development of rural areas. Women entrepreneurship in rural areas indicated will increase the local economy, creating employment opportunities, and decreasing the poverty currently. One province in Indonesia that successfully promotes the fashion industries to local and international tourist is West Java. This study aims to analyze the effect of network development strategy toward the women entrepreneurs’ satisfaction. Hypothesis were tested by multivariate statistics- Partial Least Square. The population is owners or managers of SMEs in fashion or garment industries. Stratified random sampling is occupied to get 78 women entrepreneurs in West Java. This study shows that network strategy is significantly influenced the women entrepreneurs’ satisfaction Proactive entrepreneur is proved to positively strengthen the impact of network strategy on the women entrepreneurs’ satisfaction. This result becomes a guide for SMEs, especially in fashion or garment industry to support the tourism of West Java.